2015
DOI: 10.1103/physrevlett.115.088303
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence Model for Crumpled Globules Formed in Polymer Collapse

Abstract: The rapid collapse of a polymer, due to external forces or changes in solvent, yields a long-lived "crumpled globule." The conjectured fractal structure shaped by hierarchical collapse dynamics has proved difficult to establish, even with large simulations. To unravel this puzzle, we study a coarse-grained model of in-falling spherical blobs that coalesce upon contact. Distances between pairs of monomers are assigned upon their initial coalescence, and do not "equilibrate" subsequently. Surprisingly, the model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
(85 reference statements)
0
23
0
Order By: Relevance
“…After α L reaches its minimum, it increases due to mixing in the already collapsed "blobs" up to the maximal value α L = 1/2, corresponding to the equilibrium globule state. Theoretical studies and computer simulation results show [11][12][13]16], that chain segments, which form distinct blobs, remain segregated for a relatively long time and can not freely mix immediately after coagulation of blobs due to topological constraints. This happens because chain can not cross itself, and there are no open chain ends (except the two terminal ends), as in the polymer solution of many chains.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After α L reaches its minimum, it increases due to mixing in the already collapsed "blobs" up to the maximal value α L = 1/2, corresponding to the equilibrium globule state. Theoretical studies and computer simulation results show [11][12][13]16], that chain segments, which form distinct blobs, remain segregated for a relatively long time and can not freely mix immediately after coagulation of blobs due to topological constraints. This happens because chain can not cross itself, and there are no open chain ends (except the two terminal ends), as in the polymer solution of many chains.…”
Section: Methodsmentioning
confidence: 99%
“…Blobs grow in size continuously, merging together, and the chain collapses globally. However, size distribution of blobs during collapse under active compression can be very nontrivial [12]. It is also unclear how chain structure changes in time inside blobs during collapse, and theoretical works do not describe this evolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the relaxation properties of the elastic network of contacts in a crumpled globule, we showed that the dynamic properties of hierarchically folded polymer chains in globular phase are similar to those of natural molecular machines (like myosin, for example). We discuss the potential ways of implementations of such artificial molecular machine in computer and real experiments, paying attention to the conditions necessary for stabilization of crumples under the fractal globule formation in the polymer chain collapse [64] (see also the work on coalescence of crumples in polymer collapse [96]). …”
Section: B Where To Go?mentioning
confidence: 99%
“…For most such polymer systems, at distances much larger than the persistence length, mean spatial distance, R, monotonically increases, and contact frequency, P c , monotonically decreases as a function of the number of intervening monomers, s. Given a pair of loci, the number of monomers between them, s, fully specifies their contact probability and spatial distance. For example, in a random walk, the distance between monomers, R(s) is proportional to s 1/2 , while the contact probability is inversely proportional to the volume occupied by a section of the polymer, P c (s) ~ R(s) -3 = s -3/2 Slightly different, yet still directly proportional, relationships can be seen in other polymer ensembles, including the fractal globule and unknotted globules (Bunin and Kardar, 2015;Imakaev et al, 2015a) (to be discussed further in future work). Here, we see this typical, monotonic behavior, in the region of our simulated polymer that lies far from the dynamic loop (Supplemental Fig 2).…”
Section: Simulations Can Reconcile Contact Frequency and Spatial Distmentioning
confidence: 99%